High Counts of CD68+ and CD163+ Macrophages in Mantle Cell Lymphoma Are Associated With Inferior Prognosis - Li, Philippa; Yuan, Ji; Ahmed, Fahad Shabbir; McHenry, Austin; Fu, Kai; Yu, Guohua; Cheng, Hongxia; Xu, Mina L.; Rimm, David L.; Pan, Zenggang (Frontiers in Oncology, 2021)
Background: Lymphoma-associated macrophages (LAMs) are key components in the lymphoma microenvironment, which may impact disease progression and response to therapy. There are two major subtypes of LAMs, CD68+ M1 and CD163+ M2. M2 LAMs can be transformed from M1 LAMs, particularly in certain diffuse large B-cell lymphomas (DLBCL). While MCL is well-known to contain frequent epithelioid macrophages, LAM characterization within MCL has not been fully described. Herein we evaluate the immunophenotypic subclassification, the expression of immune checkpoint molecule PD-L1, and the prognostic impact of LAMs in MCL. Materials and methods: A total of 82 MCL cases were collected and a tissue microarray (TMA) block was constructed. Immunohistochemical staining was performed using CD68 and CD163, and the positive cells were recorded manually in four representative 400× fields for each case. Multiplexed quantitative immunofluorescence assays were carried out to determine PD-L1 expression on CD68+ M1 LAMs and CD163+ M2 LAMs. In addition, we assessed Ki67 proliferation rate of MCL by an automated method using the QuPath digital imaging analysis. The cut-off points of optimal separation of OS were analyzed using the X-Tile software, the SPSS version 26 was used to construct survival curves, and the log-rank test was performed to calculate the p-values. Results: MCL had a much higher count of M1 LAMs than M2 LAMs with a CD68:CD163 ratio of 3:1. Both M1 and M2 LAMs were increased in MCL cases with high Ki67 proliferation rates (>30%), in contrast to those with low Ki67 (<30%). Increased number of M1 or M2 LAMs in MCL was associated with an inferior OS. Moreover, high expression of PD-L1 on M1 LAMs had a slightly better OS than the cases with low PD-L1 expression, whereas low expression of PD-L1 on M2 LAMs had a slightly improved OS, although both were not statistically significant. Conclusions: In contrast to DLBCL, MCL had a significantly lower rate of M1 to M2 polarization, and the high levels of M1 and M2 LAMs were associated with poor OS. Furthermore, differential PD-L1 expressions on LAMs may partially explain the different functions of tumor-suppressing or tumor-promoting of M1 and M2 LAMs, respectively.